Attitude, subjective norm, and perceived behavioral control as predictors of the intention of mental health seeking among undergraduate students - Lean, Ying Tong; Low, Lee Sang; Cheam, Ronald Jun Xian (2024)
Although undergraduate students commonly face psychological and emotional difficulties, they often have a poor intention to seek mental health care. The present study aims to study the predictive effects of attitude, subjective norm, perceived behavioural control, and help-seeking intention among undergraduate students. The study was conducted using purposive sampling, and a cross-sectional research study. Questionnaire were distributed through Qualtrics link and QR code. A total of 230 responses were obtained for this study, however only 181 responses remained in final data analyses after data cleaning. The inclusion criteria for participants in this study were i) undergraduate student, ii) aged 18 and above, and iii) Malaysian. The current findings showed that attitude and perceived behavioural control significantly and positively predict help-seeking intention among undergraduate students, except subjective norm did not significantly predict. Effective interventions should be developed based on these significant predictors to foster a supportive environment among undergraduate students that encourages proactive mental health-seeking intentions. For example, awareness campaigns can spread information about available resources and promote positive attitudes toward seeking help.